GPS‐based satellite formation flight simulation and applications to ionospheric remote sensing. Issue 1 (27th February 2020) - Peng, YuXiang; Scales, Wayne A.; Edwards, Thom R.
Abstract: The Virginia Tech Formation Flying Testbed (VTFFTB), a GNSS‐based hardware‐in‐the‐loop (HIL) simulation testbed for spacecraft formation flight, is developed and applied to ionospheric remote sensing. The current VTFFTB consists of GNSS RF hardware signal simulators, multi‐constellation multi‐frequency GNSS receivers, a navigation and control system, an STK visualization system, and an ionospheric remote sensing system. GPS signals are emulated using GNSS simulator scenarios that include ionospheric phenomena. A formation of two spacecraft ("chief" and "deputy") is considered. GNSS receiver data are used to produce space‐based Total Electron Content (TEC) and scintillation measurements. A reference low Earth orbit (LEO) scenario is benchmarked with past simulation results to validate functionality. A LEO formation flying mission is designed to probe two Equatorial Spread F (ESF) scenarios with plasma bubbles. The results investigate the structure of ionospheric irregularities and demonstrate that the GPS‐based satellite formation is able to measure vertical electron density by differencing 1D GPS vertical TEC.